Поисковые работы в среднем течении Северского Донца (Юго-Восточная Украина) - Колесник, А.В.; Давыденко, В.В. (Археологічні дослідження в Україні, 2010)
As a result of a goal-seeking archaeological prospecting conducted by the expedition of the Donetsk National University in 2008 and 2009 in the Donets River region the authors succeeded to establish the dense settling of certain terraced areas of the right bank of the Siverskyi Donets River. In the core of this phenomenon is the concentration of various sources in the basin of the river and on the right bank slopes. The monuments belong to various epochs.